Islamization in the Discourse of Islamic Economics Integration - Waluyo, Agus (Hikmatuna : Journal for Integrative Islamic Studies, 2020)
The model of science integration is conducted with different approaches. One model of integration in Islamic economics is the Islamization approach. This study aims to describe Islamization as an integrated approach in the field of Islamic economics. This study is a literature review supported by data and analysis with main sources from books, articles and websites. The research findings show that the Islamization has an impact on the development of scientific disciplines. In the midst of the strong offer of various integration paradigms, the Islamization as the mainstream approach is relevant to development of Islamic scientific integration, including Islamic economics. To realize the integration of Islamic economics, activists of Islamization must continue formulating theories and develop methodologies of Islamic economics with an integrative paradigm. The implication of this study is that the efforts are still needed so that Islam is not only a tool of justification for economic theory in the process of the movement of science Islamization.